2022
DOI: 10.1080/09506608.2022.2145359
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of electrodeposition of Bi2Te3and its thermoelectric applications in miniaturized power generation and cooling

Abstract: Thermoelectric (TE) technology enables direct conversion between thermal and electrical energies and thus has been regarded as an alternative for energy harvesting and refrigeration. Bismuth telluride (Bi 2 Te 3 ) is the most widely used TE material at room temperature due to its high figure of merit (∼1). Since the first publication on the electrodeposition of Bi 2 Te 3 films in 1994, a large number of publications has emerged in the last two decades, owing to its advantages such as simple and safe preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 238 publications
0
2
0
Order By: Relevance
“…19 Electrodeposition is a highly productive and adaptable method that offers high deposition rates, scalability, ease of operation, low cost, and precise control over a variety of parameters such as composition and morphology. 6 Padmanathan et al reported that increasing the Cu content in electrodeposited CuBiTe 20 or even in the Te film 21 improved the power factor. The Cu-doping reduced the carrier concentration, leading to a larger Seebeck coefficient at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…19 Electrodeposition is a highly productive and adaptable method that offers high deposition rates, scalability, ease of operation, low cost, and precise control over a variety of parameters such as composition and morphology. 6 Padmanathan et al reported that increasing the Cu content in electrodeposited CuBiTe 20 or even in the Te film 21 improved the power factor. The Cu-doping reduced the carrier concentration, leading to a larger Seebeck coefficient at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical raw materials utilized in ED are typically oxides or salts, which are more economically viable. Additionally, ED can be conducted directly in ambient air, eliminating the need for high vacuum or elevated temperatures [44]. It also can be seamlessly integrated with complementary metal-oxide-semiconductor (CMOS) technology, facilitating the fabrication of high-power-density TE generators or coolers.…”
mentioning
confidence: 99%